The Study of Processing Carrot Brem as an Alternative Source of b-Carotene Products - . Triyani; Lilik N Yuliati; Rizal Damanik (Media Gizi dan Keluarga, 2000)
The purpose of this research was (1) to study the process of making carrot brem as an alternative source of b-carotene products, and (2) to study the chemical characteristics of carrot brem produced. The research was carried out during April-June 1999 at the Food Experimental Laboratory of Department of GMSK, Faculty of Agriculture IPB Bogor. Several levels of dextrin (27%, 30% and 33%) were added to the carrot juice to produce carrot brem in comparison to the addition of sticky rice to the carrot juice. The carrot brem produced was then analyzed for its chemical characteristics and was evaluated by 30 trained-panelist for its organoleptics performance. The results showed that that the addition of 30% dextrin had no significant effects (p>0,05). However, this level of dextrin had significant effects (p